2017
DOI: 10.1158/1535-7163.mct-16-0567-t
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase G9a Drives Chemotherapy Resistance by Regulating the Glutamate–Cysteine Ligase Catalytic Subunit in Head and Neck Squamous Cell Carcinoma

Abstract: Transient chemotherapeutic response is a major obstacle to treating head and neck squamous cell carcinomas (HNSCC). Histone methyltransferase G9a has recently been shown to be abundantly expressed in HNSCC, and is required to maintain the malignant phenotype. In this study, we found that high G9a expression is significantly associated with poor chemotherapeutic response and disease-free survival in HNSCC patients. Similarly, G9a expression and enzymatic activity were elevated in cisplatinresistant HNSCC cells.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 46 publications
2
25
0
1
Order By: Relevance
“…Several reports have indicated that EHMT2 expression and enzymatic activity were associated with malignant behaviors, such as tumor growth, cell invasion, cancer stem cell phenotypes and survival, in various cancer types 23 25 . Liu et al 26 recently found that EHMT2 protected head and neck squamous cell carcinoma cells against cisplatin by increasing GSH expression, suggesting that EHMT2 is a promising target for the prevention of chemotherapy resistance in patients undergoing cancer treatment. Our results also demonstrated that EHMT2 expression and enzymatic activity levels were upregulated in NSCLC EGFR-TKI-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that EHMT2 expression and enzymatic activity were associated with malignant behaviors, such as tumor growth, cell invasion, cancer stem cell phenotypes and survival, in various cancer types 23 25 . Liu et al 26 recently found that EHMT2 protected head and neck squamous cell carcinoma cells against cisplatin by increasing GSH expression, suggesting that EHMT2 is a promising target for the prevention of chemotherapy resistance in patients undergoing cancer treatment. Our results also demonstrated that EHMT2 expression and enzymatic activity levels were upregulated in NSCLC EGFR-TKI-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…GCL is composed of a large catalytic subunit (GCLC) and a small modified subunit ( 5 , 8 ). GCLC was recently reported to be involved in tamoxifen resistance in breast cancer ( 9 ) and cisplatin resistance in head and neck squamous cell carcinoma ( 10 ). Cysteine is mainly supplied from outside of the cell as a form of cystine via a cystine-glutamate transporter, xc(-), which was previously reported to be related to cancer chemoresistance ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, G9a expression is closely associated with tumorigenesis, metastasis and drug resistance in many cancers [36]. We previously reported that G9a promotes tumor growth via enhancing HP1α and silencing APC2 expression (19).Researchers have shown that G9ais transcriptionally regulated by special AT-rich sequence-binding protein 2 (SATB2).…”
Section: Discussionmentioning
confidence: 99%